2012
DOI: 10.4103/1755-6783.92877
|View full text |Cite
|
Sign up to set email alerts
|

Infection control practices among doctors and nurses in a tertiary care hospital

Abstract: Background: Basic infection control measures in any healthcare setup can reduce the rates of healthcareassociated infections. A study to assess the knowledge and practice of 400 healthcare personnel regarding hospital infection control practices was performed. Materials and Methods: A structured questionnaire was distributed to the study group and collected the same day. Knowledge and practices of 329 nurses and 71 doctors regarding hand hygiene, SPs, hospital environmental cleaning and needle stick injury wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…Jain et al, (24) supported the present study finding and demonstrated that considerable improvement regarding the respondents knowledge and implementation of specific infection control precautions post educational program.…”
Section: Discussionsupporting
confidence: 79%
“…Jain et al, (24) supported the present study finding and demonstrated that considerable improvement regarding the respondents knowledge and implementation of specific infection control precautions post educational program.…”
Section: Discussionsupporting
confidence: 79%
“…1,5 Like our study, other studies in India, 7,8 Italy 9 and Ghana 10 identified the nurses' and healthcare students' lack of knowledge regarding HAI. Hand hygiene has always been considered one of the cornerstones of infection control, but adherence to recommendations for hand-hygiene practices remains extremely low in most healthcare settings.…”
Section: Discussionmentioning
confidence: 42%
“…Strict adherence by healthcare workers to standard precautions usually prevents a considerable percentage of these risks. 4 Health care workers' knowledge of standard and isolation precautions has been reported to be insufficient 5 and specialised training must be received before a healthcare worker undertake any patient procedure involving sharp devices. 6 also Mukerji et al 7 reported that interventions to improve hand hygiene compliance are challenging to implement and sustain with the need for ongoing reinforcement and education.…”
Section: Introductionmentioning
confidence: 99%